A mutant of hepatitis B virus X protein (HBxΔ127) enhances hepatoma cell migration via osteopontin involving 5-lipoxygenase - Zhang Xuan; Ye Li-hong; Zhang Xiao-dong (Acta Pharmacologica Sinica, 2016)
Aim: To explore a novel function of a mutant of the hepatitis B virus X protein (HBxΔ127) in the promotion of hepatoma cell migration. Methods: The effect of HBxΔ127 and wild type HBx on the migration ability of hepatoblastoma HepG2 cells were examined using wound healing assays in stable transfection systems. The full-length osteopontin(OPN) promoter sequence was cloned into the pGL3-Basic plasmid. The promoter activities of OPN in stably HBxΔ127-transfected hepatoblastoma HepG2 (HepG2-XΔ127) and hepatocellular carcinoma H7402 (H7402-XΔ127) cells were determined using luciferase reporter gene assays. The mRNA expression levels of OPN were detected by RT-PCR. And the effect of MK886, a specific inhibitor of 5-lipoxygenase (5-LOX), on OPN promoter activity and mRNA expression in HepG2-XΔ127 and H7402-XΔ127 cells were examined using luciferase reporter gene assays and RT-PCR, respectively. Finally, the migration ability of HepG2-XΔ127 was observed after treatment with siRNA targeting OPN mRNA and HBx mRNA using wound healing assays. Results: HepG2-XΔ127 cells exhibited a greater capacity for wound repair compared to HepG2-X cells. The promoter activity and mRNA expression levels of OPN were also increased in HepG2-XΔ127 and H7402-XΔ127 cells. Moreover, MK886 abolished the HBxΔ127-mediated upregulation of OPN. Wound healing assays demonstrated that the migration ability of HepG2-XΔ127 cells can be suppressed by treatment with siRNA targeting OPN mRNA and siRNA targeting HBx mRNA. Conclusion: HBxΔ127 strongly promotes hepatoma cell migration via activation of OPN involving 5-LOX.